Characterization of Leptin Receptor+ Stromal Cells in Lymph Node - Jiang, Liwei; Yilmaz, Mine; Uehara, Mayuko; Cavazzoni, Cecilia B.; Kasinath, Vivek; Zhao, Jing; Naini, Said Movahedi; Li, Xiaofei; Banouni, Naima; Fiorina, Paolo; Shin, Su Ryon; Tullius, Stefan G.; et al. (Frontiers in Immunology, 2022)
Lymph node (LN)-resident stromal cells play an essential role in the proper functioning of LNs. The stromal compartment of the LN undergoes significant compensatory changes to produce a milieu amenable for regulation of the immune response. We have identified a distinct population of leptin receptor-expressing (LepR+) stromal cells, located in the vicinity of the high endothelial venules (HEVs) and lymphatics. These LepR+ stromal cells expressed markers for fibroblastic reticular cells (FRCs), but they lacked markers for follicular dendritic cells (FDCs) and marginal reticular cells (MRCs). Leptin signaling deficiency led to heightened inflammatory responses within the LNs of db/db mice, leakiness of HEVs, and lymphatic fragmentation. Leptin signaling through the JAK/STAT pathway supported LN stromal cell survival and promoted the anti-inflammatory properties of these cells. Conditional knockout of the LepR+ stromal cells in LNs resulted in HEV and extracellular matrix (ECM) abnormalities. Treatment of ob/ob mice with an agonist leptin fusion protein restored the microarchitecture of LNs, reduced intra-LN inflammatory responses, and corrected metabolic abnormalities. Future studies are needed to study the importance of LN stomal cell dysfunction to the pathogenesis of inflammatory responses in type 2 diabetes (T2D) in humans.